Al-Wujūhu Al-Ḍoifaħ ‘Indal Imām Ibn Juzay Fī Tafsīr Min Awali Sūraħ Al-Fātihaħ Ila Nihayati Sūraħ Al-Baqaraħ: الوجوه الضعيفة عند الإمام ابن جزي في تفسيره من أول سورة الفاتحة إلى نهاية سورة البقرة - M Gozali Tayib; Ammar Mohammed Abdo Al-Gumaei; Heggy Fajrianto (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Al-Qur'an (STIQ) ZAD Cianjur, 2020)
These studies aim to define the weak sayings of Imam Ibn Juzi in his interpretation of the facilitation of the sciences of revelation, in order to know the meanings of the correct Qur’an by explaining the reason why the Imam weakened the sayings. These studies follow the analytical descriptive approach, by following the weakness of Imam Ibn Juzy in his interpretation of the facilitation of the sciences of revelation, then collecting, classifying, presenting, and analyzing them, according to the origins and rules of interpretation. This study proved that the explanatory sayings weakened by Imam Ibn Juzi in his interpretation from the beginning of Surat Al-Fatihah to the end of Surat Al-Baqarah thirteen places, and this study revealed that the explanatory sayings weakened by Imam Ibn Juzy are not all correct, and the subject of weak faces in this interpretation, which should be necessary that Interpretation teachers care about it.